Do Rural Roads Reduce Poverty? A Spatial and Panel Analysis of Village Fund Investments in Kebumen, Indonesia (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
This study examines whether Village Fund investments in rural road connectivity effectively reduce poverty in Kebumen Regency, the poorest region in Central Java. Using village-level data from 2022 to 2024, the analysis combines spatial clustering methods (Moran’s I and LISA) with panel data models to assess both geographic patterns and causal relationships. Spatial results reveal persistent and intensifying poverty clusters in the northern hilly areas, while low-poverty clusters remain concentrated in the southern coastal zone. Village Fund road investments also show uneven spatial concentration, with increasing clustering over time but limited alignment with poverty hotspots. Panel data analysis finds that although road budget allocations are statistically associated with reductions in village poverty rates, the effect size is very small and becomes insignificant once year effects are included, suggesting that broader macroeconomic conditions outweigh local infrastructure spending. Geographic constraints—particularly slope and elevation—significantly moderate road investment effectiveness, indicating weaker impacts in more difficult terrains. Overall, the findings show that rural road investments under the Village Fund have had only marginal short-term effects on poverty reduction. The study argues that future Village Fund allocations should shift toward human capital and livelihood-based programs rather than prioritizing physical infrastructure in already connected regions.